PENGARUH PENGALAMAN AUDITOR, KEAHLIAN AUDITOR, INDEPENDENSI, TEKANAN KETAATAN, DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGEMENT - Nadya Vincent; MARIA STEFANI OSESOGA (Universitas Multimedia Nusantara, 2019)
This research aims to determine the effect of auditor's experience, auditor's expertise, independence, compliance pressure, and task complexity on audit judgement. The data used in this study was primary data. This research was conducted by distributing questionnaires to auditors working in Public Accounting Firm located in Jakarta and Tangerang in 2018-2019. Auditors who become respondents were auditors with work experience of more than three years and educated at least bachelor degree (S1) in accounting. There were 208 questionnaires distributed for this research, but only 166 questionnaires were returned and 104 questionnaires were used in this research using multiple linear regression. The result of this research are (1) auditor’s experience has no effect on audit judgement, (2) auditor’s expertise has a significant effect on audit judgement, (3) independence has a significant effect on audit judgement, (4) compliance pressure has no effect on audit judgement, (5) task complexity has a significant effect on audit judgement, and (6) auditor’s experience, auditor’s expertise, independence, compliance pressure, and task complexity have a significant effect on audit judgement.